DIGITALISASI BANK SAMPAH SEBAGAI OPTIMALISASI PENGELELOAAN SAMPAH DAN PENDAYAGUNAAN MASYARAKAT DI DESA PEJATEN, KECAMATAN KEDIRI, KABUPATEN TABANAN, BALI - tiawan; Gede Andry Dewa Kusuma; Angel Kurniawati Hematang (Universitas Majalengka, 2023)
Pejaten Village is one of the villages in Kediri District, Tabanan Regency, Bali Province. Pejaten Village or commonly known as Tile Village because of the production of good quality roof tiles in this Village. Behind the production of good quality roof tiles, Pejaten Village has now developed a Garbage Bank. The Garbage Banks in Pejaten Village are 5 Banjars out of 8 Banjars with 1 Main Garbage Bank which is shaded under Pejaten Village. However, the Garbage Bank that is used is still conventional, still does traditional recording and requires a lot of energy in recording and calculating this Garbage Bank. The Garbage Bank in Pejaten Village also faces inconsistent collectors who receive results from the Garbage Bank from Pejaten Village. With the existence of the Digital Waste Bank, in terms of recording and calculating the value of waste exchanged per each resident in Pejaten village, it will be more accurate and reduce the number of workers needed. The Digital Garbage Bank is an application that contains waste balances that have been exchanged by residents at the waste bank and this balance can be exchanged once every 6 months in the form of groceries and compost. As well as socialization about waste sorting and waste utilization which will be able to build Pejaten villagers to understand more about adding value to the use of waste after it has been sorted.